The Effect of Elderly Gymnastics on Lowering Blood Pressure in Elderly Patients with Hypertension - Mufidzatul Zulfa Laili Askhad; Adang Suherman; Mohammad Zaky (Journal of Physical Education Health and Sport, 2026)
Hypertension affects 50-60% of the elderly population due to a decrease in the physiological function of blood vessels that are at risk of causing cardiovascular complications. Blood pressure control is not only carried out with antihypertensive drugs, but also requires a non-pharmacological approach. One of the efforts that can be made is elderly gymnastics. Therefore, this study aims to analyze the effect of elderly gymnastics on the reduction of systolic and diastolic blood pressure in elderly with hypertension, both those who take antihypertensive drugs and those who do not, at Wisma Lansia J. Soenarti Nasution. This study uses a quantitative approach with an ex post facto design. The study subjects amounted to 20 elderly people with a total sampling technique. Blood pressure measurement was carried out using a digital sphygmomanometer after the implementation of elderly gymnastics during the period from September – December. Data were analyzed using the Shapiro-Wilk normality test and the Mann-Whitney non-parametric test. The results of the analysis show the value of Asymp.Sig.(2-tailed) of 0.000 (p < 0.05) across systolic and diastolic blood pressure measurements in each period, indicating a statistically significant difference. Elderly gymnastics was shown to have a blood pressure lowering and stabilizing effect in both groups, with blood pressure relatively lower in the group without the consumption of antihypertensive drugs. Elderly gymnastics has a significant effect on blood pressure control in the elderly with hypertension, both as non-pharmacological intervention and as a complementary therapy to antihypertensive treatment. These findings support the sustainable intergration of elderly gymnastics in elderly health programs.